An Investigation into the Enablers and Barriers of Green Economy Management - Kundu, Nirmal; Bhar, Chandan; Pandurangan, Visvesvaran (Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
The term â€˜green economyâ€™ was first coined by a group of leading environmental economists in UK in 1989 in a report entitled â€˜Blueprint for a Green Economyâ€™. The green economy is one in which value and growth is maximized across the whole economy, while natural assets are managed sustainably. Sustainable system is based on â€œtriple bottom lineâ€ thinkingenvironment, economic and social or in other words planet, profit and people respectively, being called â€œthe three Psâ€. Green economy is an important tool for sustainable development; one that is inclusive and can drive economic growth, employment and poverty eradication, whilst maintaining the healthy functioning of the Earthâ€™s ecosystems. Although green economy is most natural and being practiced since the inception of agricultural society, however, with the progress of civilization, as it is being preached more and more, it is becoming a distant reality. The objective of this article is to study the status of green economy in great detail, with the success and failure story of the green economy across the globe and investigate the enablers (political pressure, international law, global policy and framework, reverse technology transfer, reverse innovation, inclusive innovation, humanitarian innovation etc.) and barriers (lack of foresight, lack of vision and knowledge, lack of involvement and commitment, business risk etc.) of green economy. The research methodology used in this study is a combination of literature review, case studies and key informant interviews. The literature review includes both published as well as unpublished sources of literature. Case studies have been mainly taken from Wind industry which by nature is â€˜greenâ€™. In case of key informant interviews, informal telephonic discussions have been carried out with the key executives of the organizations (industry, university, research institutions and government officials) who are actively engaged and taking lead role in the development of green economy.